The Role of the Risk Committee in Mitigating Risk-Taking Behavior Arising from Agency Conflicts in Indonesian Banking - widya rizki eka putri; Fatkhur Rohman; Rialdi Azhar; Khairullah Taj (Universitas Bangka Belitung, 2026)
This study examines the effect of agency conflict on risk-taking behavior in the Indonesian banking industry and evaluates the role of the Risk Committee as an internal governance mechanism. Three structural attributes of the Risk Committee—independence, expertise, and meeting frequency—are assessed as moderating variables that may strengthen internal oversight over managerial decision-making. Using panel data from conventional banks in Indonesia for the 2017–2023 period, the results show that agency conflict positively and significantly increases risk-taking behavior, indicating potential managerial opportunism arising from misaligned principal–agent interests. Among the moderating variables, Risk Committee expertise proves the most effective in weakening the influence of agency conflict, while meeting frequency also demonstrates a significant moderating effect. Conversely, committee independence does not exhibit a statistically significant moderating role. Overall, the findings underscore the importance of substantive governance quality—particularly professional competence and supervisory intensity—in mitigating the adverse effects of agency conflicts. These insights offer relevant implications for regulators and stakeholders.